Desain Konseptual UAV Long Endurance Low Altitude (LELA) untuk Misi Pengawasan Jarak Jauh - Fathi, Syahrul; Sukhairi, Teuku Ariessa; Jayadi, Farid; Munawir, Al; Masykur, Masykur; Rizki, Julia (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
This study discusses the conceptual design process of an Unmanned Aerial Vehicle (UAV) featuring Long Endurance Low Altitude (LELA) characteristics, intended for long-range surveillance missions. The design is based on a quantitative approach through the estimation of initial performance parameters such as wing loading, power loading, maximum lift coefficient (CLmax), and lift-to-drag ratio (L/D). Technical data were obtained from literature and preliminary numerical calculations, then used to determine the main geometric dimensions and power requirements of the aircraft. The design results show that a UAV with a take-off weight of 15.08 kg, wing area of 0.2317 m², and cruise power of 67.34 Watts is capable of flying for 79 minutes with an L/D ratio of 13.69. The center of gravity (CG) is located 0.454 m from the aircraft nose, indicating good longitudinal stability. This research provides an essential early- stage contribution as a foundation for further development in the preliminary design phase.